Development of a retrofit layer with an embedded array of piezoelectric sensors for transient pressure measurement in maritime applications. (May 2023) - Riccioli, Filippo; Huijer, Arnaud; Grasso, Nicola; Rizzo, Cesare M.; Pahlavan, Lotfollah
Abstract: Measurement of transient pressure distribution on maritime structures is important for the assessment of the hydrodynamic loads applied. The commonly used pressure sensors are mostly bulky, need to be bolted to the structure, and/or only provide point-wise measurements. In this paper, an elastic matrix layer with a network of embedded piezoelectric sensors is proposed to address these issues. For experimental validation, a 400 × 400 × 5 mm epoxy layer is fabricated embedding 25 piezoelectric sensors on a square grid in accordance with Gauss-Lobatto-Legendre points. A finite element based inverse procedure is developed to reconstruct the pressure field from the electric potentials measured by the piezoelectric transducers. Feasibility of the concept is evaluated by measuring and reconstructing the pressure field generated by a travelling wave in a water tank. Sensitivity of the layer is also investigated through the experiments. The results indicate that the retrofit layer is capable of pressure field reconstruction, and that the presence of disturbances on the sensing surface does not affect the measurements in a notable way, while non-ideal conditions of the mounting can have a significant impact on the accuracy of the measurements. The results highlight the potential of the concept in pressure distribution measurements. Highlights: Measurement of transient pressure distribution on surface of maritime structures. FEM-based inverse approach to reconstruct the pressure field from measured voltages. Retrofit layer capable of reconstructing the transient pressure distribution.